The Dark Sectos of the Universe in a Neutron Star Environment - Araújo, Loreany; Sales de Lima, José Ademir; Lugones, Germán (Cadernos de Astronomia, 2026)
In this work, we present some results from a series of studies investigating the effects of incorporating a dark-sector component into the structure of neutron stars. In particular, we examine how dark matter and dark energy fluids can alter the macroscopic properties of these compact objects. Two main scenarios are considered: the coexistence of three fluids coupled solely through gravity and the presence of interactions among them.We find that the impact of the dark-energy component on stellar structure depends on the equation-of-state parameter (ω), potentially leading to configurations with larger radii and higher maximum masses, whereas values of ω < −1 tend to weaken the hydrostatic support against gravitational collapse. More generally, larger relative fractions of the dark sector result in smaller stellar masses and radii due to their limited contribution to the total pressure. Across all scenarios considered, only specific parameter ranges were found to be consistentwith current observational constraints, with the requirement of supporting maximum masses of at least (2 M⊙) providing the most stringent constraint.
Keywords: compact objects; dark energy; dark matter; mass-radius relation